Meningkatkan Motivasi Dan Prestasi Belajar Menggunakan Model Problem Based Learning, Group Investigations, Dan Picture And Picture Di Kelas IV SDN Sungai Miai 11 - Yudha Dwi Notti Seyawan; Dessy Dwitalia Sari (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The issue highlighted in this research is the lack of motivation and the persistently low academic performance of students in Pancasila Education. The causes identified include teacher-centered instruction, limited variation in teaching models, minimal implementation of diverse teaching strategies, and the absence of evaluation methods to enhance student performance. To address these issues, the Problem Based Learning, Group Investigations, and Picture And Picture models were employed. The aim of this research is to analyze the increase in student motivation and academic performance. This study utilizes a descriptive qualitative method to provide a detailed description of the phenomena being investigated. In addition to the qualitative approach, the research also involves data collection to obtain more relevant information. The Classroom Action Research (CAR) was conducted over three sessions. The subjects of the research were the fourth-grade students of class IV B at SDN Sungai Miai 11.